Experimental investigation of a slip-line field model for a worn cutting tool - Uysal, Alper; Altan, Erhan (SAGE PUBLICATIONS LTD, 2014)
In this study, the slip-line field model developed for orthogonal machining with a worn cutting tool was experimentally investigated. Minimum and maximum values of five slip-line angles (theta(1), theta(2), delta(2), eta and psi) were calculated. The friction forces that were caused by flank wear land, chip up-curl radii and chip thicknesses were calculated by solving the model. It was specified that the friction force increased with increase in flank wear rate and uncut chip thickness and it decreased a little with increase in cutting speed and rake angle. The chip up-curl radius increased with increase in flank wear rate and it decreased with increase in uncut chip thickness. The chip thickness increased with increase in flank wear rate and uncut chip thickness. Besides, the chip thickness increased with increase in rake angle and it decreased with increase in cutting speed.
Keywords: Slip-line field model; worn cutting tool; friction force; chip up-curl radius; chip thickness; SECONDARY RAKE FACE; ADHESION FRICTION; CHIP CONTACT; INTERFACE; Engineering